The Cross-Provincial Data of Life Expectancy Effect on Pension Fund in Indonesia - Sari Lestari Zainal Ridho; Habsah Binti Haji Mohamad Sabli; Heri Setiawan (Universitas Pendidikan Ganesha, 2021)
Based on theory life cycle hypothesis of saving and consumption, it is believed that this increase in life expectancy is to be one of the reasons for participating in investing; one form of investment is pension fund. Nonetheless, there was a contrary condition between the slightly increase in life expectancy and decrease in pension fund during period of 2015 to 2019 in Indonesia. Therefore, the purpose of this study is to analyse the effect of life expectancy on pension fund total participation and the number of pension fund in provinces in Indonesia. The data presented in this research is a cross-province data of life expectancy and pension funds. The data were extracted from the published database of Statistic Indonesia and Indonesia Financial Services Authority, covering a period of 2015 to 2019. The approach in this research is a quantitative approach; with the type of research used is verification research. The collected data were analysed; using a panel data regression model on random effect assumptions with Generalized Least Squares. The finding of this research it can be concluded that there is a positive and significant effect of life expectancy on pension fund. This research paper data will assist in promoting the opportunity for pensions fund business or institution. The finding of the processed and analysed data are beneficial for the stakeholder, among other the entrepreneur, pensions fund institution, or business in order to develop precise strategy. Hence, these related institutions may better prepare for the coming opportunity in creating better future, welfare in line with the sustainability.